Three-dimensional numerical modeling of RTM and LRTM processes - Isoldi,Liércio A. (2012)
Resin Transfer Molding (RTM) is a manufacturing process in which a liquid resin is injected into a closed mold pre-loaded with a porous fibrous preform, producing complex composite parts with good surface finishing. Resin flow is a critical step in the process. In this work, the numerical study of the resin flow in RTM applications was performed employing a general Computational Fluid Dynamics software which does not have a specific RTM module, making it necessary to use the Volume of Fluid method for the filling problem solution. Examples were presented and compared with analytical, experimental and numerical results showing the validity and effectiveness of the present study, with maximum difference among these solutions of around 8%. Besides, based on the computational model for the RTM process, a new computational methodology was developed to simulate Light Resin Transfer Molding (LRTM). In this process, resin is injected into the mold through an empty injection channel (without porous medium) which runs all around the perimeter of the mold. The ability of FLUENT® package to simulate geometries which combine porous media regions with open (empty) regions was used. Two specific cases were simulated, showing the differences in time and behavior between RTM and LRTM processes.